Corporate Social Responsibility, Profitabilitas dan Ukuran Perusahaan: Sebuah Hubungan Dependensi - Kinasih, Hayu Wikan; Isthika, Wikan; Amartiwi, Tita Fi’lia (Jurusan Akuntansi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Pekalongan, 2021)
This study aims to examine the influence of profitability and company size onCorporate social Responsibility (CSR). CSR measurements are carried out using theCSR costs incurred by the company. The object of research is manufacturingcompanies listed on the IDX in 2016-2019. By using purposive sampling, weobtained 140 observations. To prove whether there is an influence betweenprofitability and company size on CSR, multiple linear regression analysis is used.The test results show that profitability and company size have an effect on CSR